The effect of trichlorobenzene solvent geometry on the morphologies of C60 nano/microcrystals produced from solution. (January 2016) - Liu, D.D.; Yu, N.S.; Liu, D.P.; He, Y.Y.; Liu, R.; Li, Q.J.; Liu, B.; Liu, B.B.
Graphical abstract: Highlights: Trichlorobenzene isomers were used to control the morphologies of C60 nanocrystals. Relationship between morphologies and structures of C60 nanocrystals was discussed. The dimensional of C60 crystals depend on the molecular structures of solvents. Abstract: C60 nano/microcrystals were synthesized from fullerene dissolved in three different trichlorobenzene isomers, to investigate the role of solvent as both shape and morphology controller in the synthesis of C60 nanocrystals. Various C60 nano/microcrystals, in particle-, sheet-, cuboid- and rod morphologies have been selectively fabricated at 80 °C using either solution evaporation or solution mixing method. The molecular structure of trichlorobenzene solvent plays a key role in the formation of different crystal morphologies, and also affects the crystal structure of synthesized samples.